Strengthening NDCs in southern Africa to be more representative of farmer interests - Sunga, Ishmael; Chevallier, Romy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Nationally Determined Contributions (NDCs) are policy instruments, mandated under the Paris Agreement, to set out a country’s selfdetermined plans to curb greenhouse gas (GHG) emissions and enhance resilience by 2030. They are bottom-up processes in which countries contextualise and self-differentiate their climate targets and contributions based on their national circumstances and priorities. These roadmaps are intended to guide future actions across all sectors and stakeholder groupings, incorporating domestic climate-related risks, challenges, priorities, and opportunities from an economy-wide perspective. In both their aspiration and implementation, NDCs are essential for ensuring that cumulative global efforts lead to net-zero emissions and climateresilient development by 2050 and that countries demonstrate commitment towards achieving the mitigation and adaptation goals of the Paris Agreement.